2002
DOI: 10.1109/tps.2002.801650
|View full text |Cite
|
Sign up to set email alerts
|

A gyrotron-traveling-wave tube amplifier experiment with a ceramic loaded interaction region

Abstract: Abstract-The design and experimental study of a 35-GHz gyrotron-traveling-wave tube (gyro-TWT) amplifier operating in the circular TE 0 i mode at the fundamental cyclotron harmonic are presented. The interaction circuit in this experiment consisted of a new type of ceramic loading that provided the required loss for stable operation. A saturated peak power of 137 kW was measured at 34.1 GHz, corresponding to a saturated gain of 47.0 dB and an efficiency of 17%, with a -3-dB bandwidth of 1.11 GHz (3.3%). Peak o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
48
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(48 citation statements)
references
References 31 publications
0
48
0
Order By: Relevance
“…For increasing high-average power capability, a TE01 mode gyro-TWT employed the periodic lossy ceramic-loaded interaction circuit has been developed at the Naval Research Laboratory (NRL). A saturated peak power of 137 kW was achieved at 34.1 GHz, a saturated gain of 47.0 dB and an efficiency of 17% with a 3 dB bandwidth of 1.11 GHz [7]. Another mode-selective TE11 mode gyro-TWT at the NRL has demonstrated a measured peak output power of 78 kW, gain 60 dB, and a 3 dB bandwidth of 4.2 GHz [8].…”
mentioning
confidence: 96%
“…For increasing high-average power capability, a TE01 mode gyro-TWT employed the periodic lossy ceramic-loaded interaction circuit has been developed at the Naval Research Laboratory (NRL). A saturated peak power of 137 kW was achieved at 34.1 GHz, a saturated gain of 47.0 dB and an efficiency of 17% with a 3 dB bandwidth of 1.11 GHz [7]. Another mode-selective TE11 mode gyro-TWT at the NRL has demonstrated a measured peak output power of 78 kW, gain 60 dB, and a 3 dB bandwidth of 4.2 GHz [8].…”
mentioning
confidence: 96%
“…In the United States, a TE 01 mode gyro-TWT has been developed at the Naval Research Laboratory (NRL), to provide the required loss for stable operation, the amplifier used a ceramic loaded interaction circuit. A saturated peak power of 137 kW was achieved at 34.1 GHz, a saturated gain of 47.0 dB, an efficiency of 17%, and a 3dB bandwidth of 1.11 GHz [7]. A mode-selective TE 11 mode gyro-TWT has demonstrated a measured peak output power of 78 kW, gain 60 dB, and a 3-dB bandwidth of 4.2 GHz [8].…”
mentioning
confidence: 97%
“…But the gyro-TWT, which can potentially provide high power and broad bandwidth operation, is far less developed [1,5,6]. A gyro-TWT explores the convective instability of the ECM in a fast-wave traveling-wave circuit as its operating principle.…”
mentioning
confidence: 99%
“…But it suffers from severe challenges from the absolute instabilities [1]. A series of experimental and theoretical researches have revealed that introducing a certain kind of attenuation in the interaction circuit is a generally feasible way to stabilize these oscillations [1,[5][6][7]. The start-oscillation current is a preferable parameter to measure the stability of the system.…”
mentioning
confidence: 99%